Giuseppe De Santis - Vitti, Antonio (Book collections on Project MUSE., 1996)
One of the founding fathers of the Neo-realist movement and a Communist dedicated to populist filmmaking, Guiseppe De Santis (b. 1917) has been a significant force in Italian cinema. In spite of his crucial contribution De Santis has received little critical recognition and his work has been largely excluded from the canon of traditional cinematic teaching. In this first book-length study of De Santis, Antonio Vitti explores the filmmaker's life and work, and addresses why he has been marginalized as a result of the politics of critical reception in Italian cinema and within the academy. Through critical analysis of such films as Riso amaro (Bitter Rice), Non c'e pace tra gli ulivi ( No Peace Among the Olives), and Cesta Duga Godinu Dana (The One-Year-Long Road), Vitti offers an informative profile of a director who refused to compromise what were often unpopular political and aesthetic principles. De Santis emerged as a strong opponent of government censorship in Fascist Italy and strove throughout his career to remain faithful to his political objectives: to create a genuine popular narrative voice, and to offer, through filmmaking, a form of entertainment for the masses and a means of promoting social and political change. At the same time, possessed of considerable technical abilities and a passion for formalized beauty and sensuality, De Santis resisted the rigid rules for socio-realistic representation dictated by the Soviet Union. He conformed neither to the mainstream nor to the leftist critical expectations of his day. He anticipated, in his own critical approach, the direction of contemporary film theory, and focused on the role of the medium itself as a means of mass communication and a repository of collective imagination.Vitti draws on his extensive personal interviews with De Santis as well as on the latter's previously unpublished writings. This volume captures the intelligence, passion, aesthetic flair, and occasionally fiery temperament of this important filmmaker.